Tracking the 3-Year Trajectory of Referrals to an Early Psychosis Intervention Service - Pitigala, Nirupamal; Zeng, Irene; Narayanan, Nishanth; Cullum, Sarah; Ng, Lillian (SAGE Publications, 2024)
AIM: To review the baseline and clinical characteristics of patients referred to a New Zealand Early Psychosis Intervention (EPI) service across a 4-year timeframe. METHOD: We compared two cohorts, and identified variables associated with being accepted or declined, and reasons for decline, by an EPI service between 2013 and 2017. RESULTS: There were 576 people with suspected psychosis referred to the EPI service for assessment: 300 (52%) were accepted, 221 (38%) declined and 55 (10%) were not processed. Reasons for being declined by EPI services were a long duration of psychosis (DUP, 48%) and no evidence of psychosis (47%). There were no significant differences between the accepted and declined group in Emergency Department presentations for self-harm or suicide attempts and acute admissions to a psychiatric inpatient unit over the 3-year follow-up period. CONCLUSION: To optimise the identification of true positive cases, EPI services require clear entry criteria. Replicating this study in other EPI services with different entry criteria may provide evidence to develop a more uniform screening process. Improved outcomes may be enhanced by measuring effectiveness and liaising with other EPI services.
Keywords: early intervention; psychosis; screening; early intervention; psychosis; screening; 4203 Health Services and Systems; 42 Health Sciences; 52 Psychology; Clinical Research; Mental Health; Serious Mental Illness; Mental Illness; Health Services; Prevention; Brain Disorders; Mental health; 3 Good Health and Well Being; 11 Medical and Health Sciences; 17 Psychology and Cognitive Sciences; Psychiatry; 32 Biomedical and clinical sciences; 42 Health sciences; 52 Psychology; Humans; Psychotic Disorders; Male; Referral and Consultation; Female; Adult; New Zealand; Early Medical Intervention; Young Adult; Mental Health Services; Patient Acceptance of Health Care; Follow-Up Studies; Suicide, Attempted; Adolescent; Humans; Follow-Up Studies; Suicide, Attempted; Psychotic Disorders; Mental Health Services; Adolescent; Adult; Referral and Consultation; Patient Acceptance of Health Care; New Zealand; Female; Male; Young Adult; Early Medical Intervention; Humans; Psychotic Disorders; Male; Referral and Consultation; Female; Adult; New Zealand; Early Medical Intervention; Young Adult; Mental Health Services; Patient Acceptance of Health Care; Follow-Up Studies; Suicide, Attempted; Adolescent